A Method for Evaluating the Risk of Exposure to COVID-19 by Using Location Data - Mendizabal-Ruiz, Eduardo Gerardo (Revista Mexicana de Ingenieria Biomedica, 2020)
One of the main reasons for the large scale spreading of COVID-19 is that many infected people are asymptomatic; therefore, as they continue with their everyday life, they likely spread the virus to more people. The diagnosis of COVID-19 is performed using real-time PCR techniques. However, their availability may be limited in certain countries or cities. Therefore, there is a significant challenge to determine a criterion of which suspect cases should be tested. A method for evaluating the risk of exposure to the COVID-19 infection using Google location data is presented in this paper. The proposed method can be fast and easily implemented using available open-source tools. This method has the potential to help to optimize the application of the COVID-19 test to suspect cases with a high risk of exposure scores. The method was test using data from four people simulating the infection of one of them. The results showed the feasibility of the proposed method to assess exposure risk. The data that can be obtained can potentially open opportunities to analyze and better understand the virus spreading patterns that may not be evident.